Supering Apis mellifera (Hymenoptera, Apidae) beehives impairs honey production and biomarker genes - Kadri, Samir Moura [UNESP]; Ribolla, Paulo Eduardo Martins [UNESP]; Alonso, Diego Peres [UNESP]; Jong, David De; Orsi, Ricardo De Oliveira [UNESP] (São Paulo - Escola Superior de Agricultura "Luiz de Queiroz", 2021)
For honey production, beekeepers add one or more supers to the hives to allow honeybees to store their products. However, the increase in hive space can affect the social and health organization in the colony, promoting stress. This study assessed the management of honey production, physicochemical honey properties, population development, and forages immune system gene expression patterns to be used as biomarker for monitoring beekeeping welfare. The treatments comprised 40 beehives divided in four treatments. Treatment 1 - control, supers added according to storage necessity. Treatments 2, 3, and 4 presented two, three, and four supers at the beginning of the experiment, respectively. T1 presented greater honey production (39.4 % increased). No difference in open brood area in the colonies was observed and honey properties and only T2 showed closed brood area higher than the other treatments. Foragers from T4 showed higher catalase and defensin gene expression at the middle-end experiment. Thus, the increasing internal space at the beginning of honey season can affect honey production and immune system of foragers. Catalase and defensin can be used as biomarkers for monitoring honey production welfare.
Keywords: apiculture; gene expression; welfare